2012
DOI: 10.1002/cta.1858
|View full text |Cite
|
Sign up to set email alerts
|

Current‐mode dual‐output ICCII‐based tunable universal biquadratic filter with low‐input and high‐output impedances

Abstract: A new tunable current-mode (CM) biquadratic filter with three inputs and three outputs using three dual-output inverting second-generation current conveyors, three grounded resistors and two grounded capacitors is proposed. The proposed circuit exhibits low-input impedance and high-output impedance which is important for easy cascading in the CM operations. It can realize lowpass, bandpass, highpass, bandreject and allpass biquadratic filtering responses from the same topology. The circuit permits orthogonal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…For designing frequency filters (fully differential, single-ended, or pseudo-differential) operational transconductance amplifiers (OTAs) [1]- [4] current follower transconductance amplifiers (CFTAs) [5], [6], current differencing transconductance amplifiers (CDTAs) [7], [8] were commonly used during the last two decades. Frequency filters can also be utilized using basic types of current conveyors (CC) [9]- [11], fully differential current conveyors (FDCC) [12], [13], differential voltage current conveyors (DVCC) [14], [15], or differential difference current conveyor (DDCC) [16], [17]. Currently, the design of function blocks is emphasized on low supply voltage and low-power consumption solutions [18]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…For designing frequency filters (fully differential, single-ended, or pseudo-differential) operational transconductance amplifiers (OTAs) [1]- [4] current follower transconductance amplifiers (CFTAs) [5], [6], current differencing transconductance amplifiers (CDTAs) [7], [8] were commonly used during the last two decades. Frequency filters can also be utilized using basic types of current conveyors (CC) [9]- [11], fully differential current conveyors (FDCC) [12], [13], differential voltage current conveyors (DVCC) [14], [15], or differential difference current conveyor (DDCC) [16], [17]. Currently, the design of function blocks is emphasized on low supply voltage and low-power consumption solutions [18]- [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, there has been much interest in current‐mode (CM) circuits in view of their many advantages over the voltage‐mode (VM) circuits such as higher bandwidth, large dynamic range, lower power consumption, greater linearity, lower sensitivity, and better accuracy . As early as in 1971, Bhattacharyya and Swamy introduced the concept of transposition and showed that VM circuits can be converted to CM circuits and vice versa by simply replacing the non‐reciprocal elements by their transposes and retaining the reciprocal subnetwork part.…”
Section: Introductionmentioning
confidence: 99%